VESPAS E ABELHAS QUE NIDIFICAM EM CAVIDADES PREEXISTENTES EM FRAGMENTOS DE FLORESTA OMBRÓFILA MISTA NA FLONA DE IRATI - Savaris, Jessica Dudek (2017)
National Forests (Flonas) are Conservation Units belonging to the group of Sustainable Use Units, and have as objective the conservation of forest resources and scientific research. The exploitation of the Flonas can be done directly by the Public Power, or by means of licitations that glimpse the development of the municipal population. Flonas are considered privileged places for scientific research, and there are no records of research on the diversity of wasps and bees in these units. Knowledge about this assembly is essential for the drafting of conservationist proposals in relation to these Flonas, because these insects are one of the most important groups for humans, providing the benefits of pollination and biological control out as arthropod species. This work aimed to investigate the cluster of wasps and bees that nest in preexisting cavities and present unpublished data on the nesting biology of Pisoxylon amenkei. It was carried out in two fragments of the Atlantic Forest, located in Flona de Irati, Paraná, one of them being an area of native forest and the other one of Araucaria Plantation. Each area received 128 nests trap 4 different diameters, which were set to 1.5 meters from the soil and collected every 15 days, for a total sampling year. This study was divided into two chapters: Chapter 1- Analyzed the assembly of wasps and bees that nest in preexisting cavities in the two fragments, seeking to investigate whether the composition, the richness and abundance of these insects are being restructured in the reforested fragment. Through the metrics analyzed in this study, it is concluded that the two fragments are different from each other, evidencing that a planting forest does not replace or recover the ecosystem services provided by these insects. Chapter 2 - Bringing unpublished information about the nesting biology of Pisoxylon amenkei Antropov, being possible to verify that the species has nesting habits very similar to others of the genus Pisoxylon. In other works carried out in the Mixed Ombrophilous Forest in the South of the country, species of this genus do not frequently nest in these forests, enhancing the importance of this study and the need for preservation of the Flona de Irati.